2021
DOI: 10.1002/phar.2627
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial and harmful outcomes of tocilizumab in severe COVID‐19: A systematic review and meta‐analysis

Abstract: Introduction:The results of studies of tocilizumab (TCZ) in COVID-19 are contradictory. Our study aims to update medical evidence from controlled observational studies and randomized clinical trials (RCTs) on the use of TCZ in hospitalized patients with COVID-19. Methods:We searched the following databases from January 1, 2020 to April 13, 2021 (date of the last search): MEDLINE database through the PubMed search engine and Scopus, using the terms ("COVID-19" [Supplementary Concept]) AND "tocilizumab" [Supplem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 131 publications
1
26
0
3
Order By: Relevance
“…We show here that blocking IL-6 signalling in pulmonary microvascular endothelial cells with Tocilizumab led to reduced LRG1 levels thus attenuating the production of a significant angiopathic factor. Studies and meta-analyses on the use of Tocilizumab in the clinics to treat severe and critically ill COVID-19 patients have reported beneficial outcomes, although critics had initially questioned the efficiency of identifying the right COVID-19 positive populations to treat with Tocilizumab 76 , 77 . If LRG1 is angiopathic in COVID-19 patients, then inhibition of IL-6 may not be sufficient to stop LRG1 as IL-1β and TNFα, both prevalent in COVID-19 infected lungs 50 , are also capable of LRG1 induction 4 .…”
Section: Discussionmentioning
confidence: 99%
“…We show here that blocking IL-6 signalling in pulmonary microvascular endothelial cells with Tocilizumab led to reduced LRG1 levels thus attenuating the production of a significant angiopathic factor. Studies and meta-analyses on the use of Tocilizumab in the clinics to treat severe and critically ill COVID-19 patients have reported beneficial outcomes, although critics had initially questioned the efficiency of identifying the right COVID-19 positive populations to treat with Tocilizumab 76 , 77 . If LRG1 is angiopathic in COVID-19 patients, then inhibition of IL-6 may not be sufficient to stop LRG1 as IL-1β and TNFα, both prevalent in COVID-19 infected lungs 50 , are also capable of LRG1 induction 4 .…”
Section: Discussionmentioning
confidence: 99%
“…To dissect this apparent incongruity, the IL-6 receptor signaling network (IL-6R network) was examined in detail. The IL-6 was consistently identified as a USR with positive z-scores (Figure 4A,B), with excessive IL-6 levels also associated with COVID-19 ARDS (49). An IL-6R network, comprising 546 genes, was generated in IPA (Supplemental Table 7A).…”
Section: Resultsmentioning
confidence: 97%
“…A series of human clinical trials have shown the benefit of anti-inflammatory treatments for COVID-19 ARDS such as corticosteroids (e.g. dexamethasone) (48) and anti-IL-6-receptor (tocilizumab) (49). When IPA Chemical Drug USRs were compared, a highly significant correlation emerged, with dexamethasone appearing with the expected negative z-score in both mice and human data sets (Figure 4C, Chemical drug).…”
Section: Resultsmentioning
confidence: 99%
“…Of all the treatments tested in COVID-19, it is the immunosuppressants/immunomodulators (corticosteroids and tocilizumab) that have demonstrated the greatest effectiveness to date [16][17][18][19][20][21][22][23][24][25]. They are especially indicated in those patients with analytical parameters of inflammation such as the patients included in the present study.…”
Section: Discussionmentioning
confidence: 99%